The NPS and Ossification: Does It Still Exist?. Issue 2 (28th January 2017) - Rinfret, Sara; Cook, Jeffrey
ABSTRACT: The US notice and comment rulemaking process has often been considered ossified or broken, but recent scholarship has questioned this claim. To address this disagreement, we use McGarity's (1992) ossification argument as a descriptive framework to structure an examination of interview data from three National Park Service rules: (1) Yellowstone National Park Rule, (2) Areas of the National Park System, Grand Canyon National Park Rule, and (3) the Gateway National Recreation Area, Sandy Hook Unit, Personal Watercraft Use Rule. We offer qualitative insights into what drives the longevity of NPS rulemaking, including analytical, scientific review, and substantive review requirements.